Towards a human resource strategy for the Caribbean - Benn, Denis (2002)
Makes observations on the conceptual and methodological issues raised in the strategy and comments on a number of specific aspets of the proposed strategy. Deals with the access to relevant research and data; health; skills and the Futures Policy Group.